A comprehensive parametric study for understanding the combined millifluidic and dripping encapsulation process and characterisation of oil-loaded capsules. (17th November 2021) - Farahmand, Atefeh; Emadzadeh, Bahareh; Ghorani, Behrouz; Poncelet, Denis
Abstract: Aim: This study aimed to utilise and optimise the millifluidic and dripping encapsulation technique to develop and characterise the oil-core capsules. Methods: Sodium alginate with Tween-20 (continuous phase) and sunflower oil (dispersed phase) were used in millifluidic system. After determining the surface and interfacial tensions and flow behaviour parameters, flow rates of phases and concentrations of alginate and Tween were optimised by the Taguchi method. The flow regime of droplets was also evaluated. Optimised millicapsules were characterised concerning morphology, dimension, encapsulation efficiency, SEM, FTIR and, DSC results. Results: Dripping flow regime during droplet formation was observed. Reducing the interfacial tension between the continuous and dispersed phases resulted in about a 10.18% reduction in diameter. Optimised millicapsules depicted spherical shape (0.03 ± 0.01) with 3.95 ± 0.05 mm size and 97.5 ± 0.2% encapsulation efficiency. The FTIR and DSC results confirmed the entrapment of oil. Conclusion: Millifluidic and dripping method effectively encapsulated sunflower oil in core-shell capsules.